Item Analysis of Arabic Midterm Exam Class X SMK Muhammadiyah 4 Yogyakarta Based on Classical Theory with R Program - Syaikha Dziyaulhaq Zein*; Ana Taqwa Wati; Anugrah Arya Bakti (Universitas Syiah Kuala, 2023)
This study produces the results of the analysis of Arabic Language Midterm Exam items at SMK Muhammadiyah 4 Yogyakarta stating that the report data obtained from the results of mathematics tests with 25 items and 88 participants as shown in the appendix. From the calculation of the difficulty level parameters in the RStudio software, good results are obtained as in table 13. Of the 25 items of the Arabic Language Midterm Exam or instruments that have been analyzed using RStudio software, it is found that the parameter value at the difficulty level for each item. Based on the table for each item, 5 items are classified as